Detection of Rail Defects Using Phased Array Ultrasonic Technique - Phrommahakul Nichapa; Kongpuang Manwika; Sani Suhaidee; Katib Anas; Sulong Fittriya (E3S Web of Conferences)
The Phased Array Ultrasonic Technique (PAUT) is an advanced non-destructive inspection method that utilizes an array of ultrasonic testing (UT) probes consisting of several small elements. The laboratory used an artificial crack on the rail steel grade 900A/ R260 test block to study the principles of PAUT and how to measure the defect’s reliability and accuracy. On-site studies were done on railroad tracks with different structures. Rail steel grade 900A/ R260, Hadfield steel, and thermite welded joints. No defects were found during the inspection at the crossing nose of the two positions. Only a darker shade of color in the area has an impact load from the wheel applied when a train changes to another direction. Inspection was also performed for the Thermit welded rail joint with two position defects. The inspection results found defects such as porosity, with an echo (A%) value exceeding 80%, but it does not require rejection according to the BART standard.